PEMBERDAYAAN MASYARAKAT SEBAGAI UPAYA PROMOTIF DAN PREVENTIF SINDROM METABOLIK PADA MASYARAKAT MELALUI PROGRAM MINCEU ANTI-MEARO - Yuniarty, Tuty; Atmaja, Ratih Feraritra Danu; Orno, Theosobia Grace; Sari, Julianti Isma; Fauzi, Ahmad Zil; Putra, Ahmat Rediansya (Universitas Mataram, 2025)
Infectious diseases remain a major public health concern due to their high morbidity and mortality rates, including conditions such as cardiovascular diseases, cancer, chronic respiratory diseases, and diabetes mellitus. Cardiovascular disease and diabetes are strongly associated with central obesity, dyslipidemia, elevated fasting blood glucose, and hypertension. Metabolic syndrome is defined as a constellation of complex metabolic abnormalities that significantly increases the risk of developing cardiovascular disease and type II diabetes mellitus. The key components implicated in the pathogenesis of metabolic syndrome include hypertension, central obesity, insulin resistance, and atherogenic dyslipidemia. This study aimed to educate the community about metabolic syndrome while simultaneously conducting early detection. The screening procedures included measurements of blood pressure, waist circumference, blood glucose levels, the measurement of total cholesterol, triglycerides, and low density lipoprotein (LDL) levels was performed using the Point of Care Testing (POCT) method. A total of 52 respondents participated in this activity, consisting of 57.7% (n=30) females and 42.3% (n=22) males. The results indicated that 92.3% (n=48) had normal blood glucose levels, 100% (n=52) had normal total cholesterol, and 21.2% (n=11) had normal LDL levels. Normal blood pressure was observed in 34.6% (n=18), while 67.3% (n=35) were found to have central obesity. Overall, 9.6% (n=5) of respondents were diagnosed with metabolic syndrome, whereas 90.4% (n=47) were not. Most respondents demonstrated metabolic risk factors such as hypertension, central obesity, and elevated LDL levels, despite having normal blood glucose and total cholesterol. These findings underscore the importance of continuous public health education and targeted interventions to prevent and reduce the prevalence of metabolic syndrome in the community.